Smoking-related diffuse cystic lung disease. (2019) - Ataya, Ali; Riley, Leonard; Fredenburg, Kristianna; Brantly, Mark
Abstract: Smoking tobacco is associated with an array of pulmonary symptoms and diseases. We describe a case of a woman with a spontaneous pneumothorax and diffuse cystic lung disease due to smoking. The presence of diffuse cystic changes in a woman is suggestive of lymphangioleiomyomatosis (LAM); however, her vascular endothelial growth factor-D was normal and surgical lung biopsy and pathology had notable absence of LAM cells and presence of intra-alveolar pigment laden macrophages and intraluminal mucostasis. Smoking-related diffuse cystic lung disease can mimic LAM and is a novel entity with only four other cases reported.